Evaluation of Different Integrated Management Strategies against Thrips (Thysanoptera: Thripidae) on Mung Bean - Mim, A. T.; Ali, M.; Yasmin, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted in the experimental field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during April‒June, 2021 to evaluate the effectiveness of integrated management approaches against thrips on mung bean. The treatments comprising seed treatment, blue sticky trap and bio-pesticides i.e. Tracer 45SC (Spinosad), Biotrin 0.5% AS, Ecomec 1.8EC or synthetic chemical insecticides i.e. Confidor 70 WG, Actara 25WG, Stargate 48SC, Novastar 56EC and an untreated control were evaluated against thrips. The efficacy of the integrated management packages differed significantly against the thrips species Megalurothrips usitatus and Thrips palmi. Among them, the integrated management approach comprising seed treatment+blue sticky trap+Stargate 48SC was the most effective and reduced the highest percent of total thrips population on top trifoliate leaves and terminal shoots (84.46% and 80.77%, respectively) at vegetative stage and on flower buds and flowers (81.26% and 80.54%, respectively) at reproductive stage of mung bean. The lowest flower bud and flower infestation (17.35% and 21.66%, respectively) and shedding (13.32% and 8.41%, respectively) and the highest number of pod (34.28 plant-1), pod length (9.29 cm), seed (10.82 pod-1), 1000 seed weight (34.10 g) and yield (1642.19 kg ha-1) of mung bean was found in the integrated management package including seed treatment+blue sticky trap+Stargate 48SC followed by the management strategy comprising seed treatment+blue sticky trap+Confidor 70 WG and seed treatment+Blue sticky trap+Actara 25WG.